Biomaterial considerations for ovarian cancer models - Kramer, Maranda; Criswell, Allyson; Sewell-Loftin, Mary Kathryn (Frontiers in Materials, 2023)
Ovarian cancer is the 5th most common and the deadliest gynecological cancer, with a five-year survival rate of less than 50 percent. Most deaths due to ovarian cancer are caused by recurrent disease, which typically corresponds to an increase in chemoresistance of the tumor cells. However, little is known about how ovarian tumor chemoresponse changes and if such changes are regulated by the tumor microenvironment (TME). Moreover, the ovarian TME, including the tissue compositions and biomechanical features, is not well-characterized primarily due to a lack of optimal models. To more effectively characterize the TME of ovarian cancer, which may help develop innovative treatment strategies, appropriate models are desperately needed. The two most utilized models include mouse models with both patient-derived xenografts and mouse or human tumor cell line derivatives, and more recently microphysiological systems (MPS). While mouse models provide This is a provisional file, not the final typeset article high levels of physiological complexity, there is virtually no control over the TME components after tumor initiation or implantation. On the other hand, MPS or organoid models permit high levels of control of initial composition but lack many features of in vivo models. Selection of appropriate components to create a TME model is paramount for generating a physiologically relevant in vitro and ex vivo systems. The importance of biomaterial or matrix selection in ovarian TME models lies in the role of these components to activate oncogenic signaling pathways either through receptor ligand interactions or mechanotransduction. Recent studies suggest that off-target or post-target effects of chemotherapies may interfere with mechanotransductive pathways. In ovarian cancer, changes in fibrous proteins, adhesive glycoproteins, and glycosaminoglycans can remodel the mechanical environment, further altering mechanotransductive pathways. Therefore, the next generation of ovarian tumor models should incorporate relevant biomaterials including hyaluronic acid (HA), collagens, fibrinogen, and fibronectin to investigate the link between matrix properties and mechanobiology with metastasis and chemoresistance.